Level of awareness in contact lens care in UiTM Puncak Alam / Fatin Nadia Mohd Khalil - Mohd Khalil, Fatin Nadia (2016)
Background: Nowadays, contact lens had become a trend especially among young adults. As one of an optical device, contact lenses will be placed directly in front of our cornea. It is a safe optical device to wear as long as the wearers practicing a correct contact lens care. However, a failure to apply a proper practice in daily routines can cause contact lens complications which might lead to visual threatening. Therefore, this study was conducted to determine the level of awareness towards contact lens care among contact lens users in UiTM Puncak Alam. Methods: In this cross sectional descriptive study, 60 participants from UiTM Puncak Alam were selected as the respondents to answer the questionnaire on their level of awareness in contact lens care. The participants who wear the contact lens were identified from UiTM Primary Optometry Clinic and Contact lens Clinic. Besides that, the questionnaires were also distributed at the faculties located in UiTM Puncak Alam. Results: Among all the participants involved, majority of 95% were female, meanwhile 5% of the participants were male and their mean age were 22.38 ± 1.485 years. The results of the study revealed that the level of awareness towards contact lens care among students in UiTM Puncak Alam was high. 83.3% of them agreed that tap water cannot be used to clean the contact lens. All of the respondents (100%) acknowledged that hand washing is essential before handling the contact lens. It was also found that 86.7% of them agreed that eye examination is necessary before prescribing the contact lens while 85% of them stated that after care assessment is also crucial after using it. Conclusion: As a conclusion this study has succeeded in determining the high level of awareness towards contact lens care in UiTM Puncak Alam. Their level of awareness in contact lens plays important roles to help in preventing any contact lens complications later.